Ex VP Dick Cheney confirmed US goal is to break up Russia, not just USSR - Norton, Ben (Geopolitical Economy Report, 2022)
Ex Vice President Dick Cheney wanted to break up Russia, not just the USSR. Balkanization is a bipartisan foreign-policy goal among top US national security state officials.
Keywords: cheney; neocon; ukraine